VD_FINDINFO Jug / 2020 / 169 vom 19. November 2019 - VD Tribunal cantonal (2019)
FIXATION DE LA PEINE, BRIGANDAGE, CHANTAGE, INFRACTION QUALIFIÉE | 140 ch. 3 CP, 140 ch. 4 CP, 156 ch. 3 CP, 47 CP, 49 al. 1 CP